A highly fluorescent AIE-active theranostic agent with anti-tumor activity to specific cancer cells. Issue 25 (19th January 2016) - Zhao, Yueyue; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract : A tetraphenylethene derivative with a structure resembling Tamoxifen is synthesized as a theranostic agent for cell imaging and anti-breast cancer therapy. Its high brightness, excellent photostability and long-term cell tracing properties enable elucidation of its working mechanism and hence provide new insights into drug development. Abstract : A tetraphenylethene derivative with a structure resembling Tamoxifen is designed and synthesized as a theranostic agent for cell imaging and anti-breast cancer therapy. Its high brightness, excellent photostability and long-term cell tracing properties enable elucidation of its working mechanism and hence provide new insights into drug development.